Pengaruh Penambahan Probiotik Pada Pakan Terhadap Kelangsungan Hidup Dan Pertumbuhan Ikan Nila (Oreochromis niloticus) dalam Sistem Akuaponik - Fauziantaka, Djordan Bembie; Pratiwy, Fittrie Meyllianawaty; Handaka, Asep Agus; Zidni, Irfan (Jurnal Perikanan Unram, 2025)
Tilapia (Oreochromis niloticus) is a freshwater fish with economic commodity value and an important commodity in the freshwater fish business in Indonesia. Problems often encountered in efforts to increase tilapia cultivation production are the reduction of empty land for cultivation activities and complex water sources in some areas. Land availability and water source supply are two main factors determining fisheries cultivation's success. Aquaponics is an alternative cultivation method that can save land and water use and optimize cultivation waste into plant biomass as a by-product with a selling value. The method used in this research is the Completely Randomized Design (CRD) experimental method, which consists of four treatments and three replications. The treatments used consist of (A) without mixing probiotics (negative control), (B) adding probiotics 5 ml.kg-1 feed, (C) adding probiotics 7.5 ml.kg-1 feed, and (D) adding probiotics 10 ml.kg-1 feed. The test tilapia were cultured in an aquaponic system with lettuce plants for 40 days with a density of 20 fish/80L. Feeding was carried out using the feeding rate (FR) method of 5% of biomass. The results obtained during the study showed that treatment C with a dose of 7.5 ml.kg-1 of feed produced positive conditions that were significantly different in terms of a specific growth rate of 2.30 ± 0.1%, 100% survival, and feed efficiency of 56.5 ± 1.6%, absolute length was 3.08 ± 0.07 cm and absolute weight was 13.14 ± 1.53 gram